Implementation of a new tool to improve the efficacy and safety of surgical handovers. (January 2015) - Blower, E.L.; MacCarrick, T.; Forster, H.; Sutton, P.A.; Vimalachandran, D.
Abstract: Aims : Compliance with European working time regulations in surgical practice has resulted in an increase in the number of clinicians caring for individual patients and subsequently an increase in the frequency of handovers. In 2007, the Royal College of Surgeons of England produced guidelines on the minimum data-set for 'safe handover'. This audit examined compliance with these guidelines before and after adopting a more detailed electronic handover 'template' with the intention of improving handover quality and patient safety.Methods : Pre-existing surgical 'take' electronic handover sheets were reviewed daily for two weeks to assess compliance with published guidance. A new proforma was introduced, training delivered and compliance re-audited. χ 2 analysis was performed to determine statistical significance.Results : The handovers of 118 patients were audited before, and 114 after, the implementation of the new proforma. Name and responsible consultant were recorded in all cases. Age (52% vs.85%, p =<0.01), location (77% vs.95%, p =<0.01), admission date (0% vs.39%, p =<0.01), medical history (82% vs.94%, p = 0.01), diagnosis (55% vs.93%, p =<0.01) and management plan (81% vs.97%, p =<0.01) showed a statistically significant improvement with the new proforma. Presenting complaint (93% vs.98%) and investigation (90% vs.90%) data remained good. Review frequency (5%vs.11%) and outstanding tasks (21%vs.27%) were poorly documented.Conclusions : Significant improvement was seen in the completeness of information handed-over following the introduction of the new proforma with likely positive implications for patient safety and standard of care. Opportunity for improvement still remains however, and more specific focussed tuition for trainees is required. Highlights: A more detailed handover template resulted in a significant improvement in practice. This is likely to have direct implications for patient safety and standard of care. Simple inexpensive measures such as this are vital to maximise NHS efficiency. Trainees informally acknowledged the quality of the tool. We recommend that all institutions undertake a critical review of their handover.